Aviation Fueling: A Cleaner, Greener Approach - Robert C. Hendricks; Dennis M. Bushnell; Dale T. Shouse (International Journal of Rotating Machinery)
Projected growth of aviation depends on fueling where specific needs must be met. Safety is paramount, and along with political, social, environmental, and legacy transport systems requirements, alternate aviation fueling becomes an opportunity of enormous proportions. Biofuels—sourced from halophytes, algae, cyanobacteria, and “weeds” using wastelands, waste water, and seawater—have the capacity to be drop-in fuel replacements for petroleum fuels. Biojet fuels from such sources solve the aviation CO2 emissions issue and do not compete with food or freshwater needs. They are not detrimental to the social or environmental fabric and use the existing fuels infrastructure. Cost and sustainable supply remain the major impediments to alternate fuels. Halophytes are the near-term solution to biomass/biofuels capacity at reasonable costs; they simply involve more farming, at usual farming costs. Biofuels represent a win-win approach, proffering as they do—at least the ones we are studying—massive capacity, climate neutral-to-some sequestration, and ultimately, reasonable costs.